Sistem Pendukung Keputusan Penentuan Kerani Timbang Lapangan Terbaik Menerapkan Metode Operational Competitiveness Rating Analysis (OCRA) - Asyahri Hadi Nasyuha; Zulkifli Zulkifli; Iwan Purnama; Agustina Sidabutar; Abdul Karim; Mesran Mesran (STMIK Budi Darma, 2022)
The weighing clerk is part of the BUMN employees whose job is to calculate incoming and outgoing income from the results of the company's raw material scales. Of course, every company engaged in this field requires quality weighing machines that can improve the quality of a company. In selecting the best field weigh-in, several criteria can be used as references, such as performance, responsibility, age, level, and number of dependents. And due to the large amount of data that is not suitable for field weighing clerks but has registered to be field team assistants, the head of the company is confused and it takes a long time to select suitable field weighing clerks to be employed. In order to assist in the selection of candidates for the weigh-in election, a decision support system is needed. The Operational Competitiveness Rating Analysis (OCRA) method is one of the supporting methods in determining the priority criteria for the selection of field weigh-in candidates. As for the results in the research on the selection of the best field weighing clerk, alternative A2 with a value of 0.583 on behalf of the Libra Purba.